TEACHERS’ PERCEPTIONS AND CHALLENGES IN IMPLEMENTING DIGITAL-BASED ISLAMIC LEARNING IN MADRASAH: A CASE STUDY AT MTS AL-KIFAYAH - Nikmah Nikmah; Supri Supri; Sri Wahyuni (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This research aims to determine teachers’ perceptions, challenges, and strategies in implementing digital-based Islamic learning in madrasahs, addressing the need to understand how technology can support religious education while maintaining alignment with Islamic values. The study employed a qualitative research design, collecting data through semi-structured interviews, classroom observations, and document reviews involving six Islamic Education (PAI) teachers at MTs Al-Kifayah. Thematic analysis was used to analyze the data, identifying recurring patterns and categorizing them into six main themes: positive perceptions of digital media, limited technological infrastructure, lack of pedagogical digital competence, concerns regarding Islamic content appropriateness, sporadic implementation with minimal curriculum integration, and adaptive strategies employed by teachers. The results indicate that teachers recognize the pedagogical potential of digital tools to enhance student engagement and comprehension but face structural, pedagogical, and ethical barriers that limit consistent integration. Despite these challenges, teachers demonstrate agency through informal learning, experimentation, and peer collaboration to optimize digital use within existing constraints. The study concludes that systematic interventions; such as targeted professional development, infrastructure improvement, curriculum integration, and provision of curated Islamic digital content are necessary to transform digital learning from an episodic activity into a sustained pedagogical practice. Further research is recommended to examine scalable models for integrating technology in Islamic education and to assess the long-term impact on student learning outcomes and moral development.